Pattern of Anorectal malformations in Gzira National Center for Pediatric Surgery (GNCPS) - Suror, Mohammed; .Nugud, F A; Taha, O; Mostafa, J (مجلة الجزيرة للعلوم الصحية; مجلد 11 عدد 1 (2015), 2015)
Background: Anorectal malformations (ARM) are one of the common clinically and socially demanding problems in the world especially in the poorly resourced countries. Patients and Methods: It is a cross-sectional descriptive hospital based study, in the period from June 2009 to December 2011 of 80 patients of ARM in Gezira National Center for Pediatric Surgery (GNCPS). History and examination in addition to invertogram and distal loopogram were the tools of assessment. Results: Eighty children with ARM were studied, 64 males and 16 females. Sixty six patients have delayed presentation. More than 61% presented from rural areas. Twenty-one (26%) patients had one or more associated congenital anomalies, with cardiac and limb anomalies being the most common associated malformation. High anomaly was found in 48.75% of patients, intermediate type was found in 5%, while 43.75% of patients had low anomaly. Conclusion: Delayed presentation entails suboptimal training of midwives and resident doctors in obstetric hospitals and nurseries to evaluate congenital defects in the newborn.